تكوين لوحة المشاهدات المنفردة للسيطرة النوعية باستخدام معدل أوقات بين الفشل مع التطبيق - ا.م .د. رزگار مغديد احمد; م.م. دشتي اسماعيل جميل; م. دلشاد محمود صالح (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study was conducted in order to use mean times of failure and another in the reliability in order to make chart individual values to quality control with the apply it. The study concluded with a conclusion that the average mean times of failure for production processes (tire factory) was in control case, because any of the samples did not locate outside the bounds of the control chart, and also configure the limits of maintenance control of predictive, which is one of the key factors that help to achieve the maintenance predictive goals, focusing new area of control over the device and detect any malfunction occurs in the production process so as to stop the production process and remove the causes of the imbalance if there is any